Perancangan Arsitektur Aplikasi Web Menggunakan Data Real Time Dari Google Form Berbasis File CSV - Joko Triyono; Erfanti Fatkhiyah; Haidar Ikram Ramadhan; Nizar Izzuddin Yatim Fadlan (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
The use of information technology is now so massive, that even reports on community activities have also used information technology. Online forms for reporting are widely used and very easy to create, with complete features. One of the products from Google is Google Forms. Starting from reservation, registration, data collection, reporting, and many activities of sending information and data can be done using this form online. The results of the data have also been presented in full, either in the form of sheets or graphic information, so that the manager or admin does not need to process it again. In the development of information needs, it turns out that the information needs from the google form are not only needed by managers or admins, but some parties need that information in real-time and do not have to log in as managers or admins, so technology is needed to distribute the data and information and processed or presented in a real-time reporting information system. In the google form, several tools have been provided such as Google APIs, Share to Sheet, CSV, etc. to share information with other parties. This study performs modeling in the design of web application architecture using real-time data from google forms based on CSV files and has been tested and produced an application model that can be pasted into other applications so that information from the google form can be conveyed without having to log in to the manager or admin of the google form.